Absorption Spectral Study of Pr(III) Complexes with L-Alanyl-L-Glutamine and N-Acetyl-L-Glutamine: Interaction Parameters, Bonding and Judd-Ofelt Intensity - Ranjana Devi, N.; Ch., Sumitra; Rajmuhon Singh, N. (Asian Journal of Chemistry, 2012)
The chemical binding of Pr(III) complexes with L-alanyl-L-glutamine (Ala-Gln) and N-acetyl- L-glutamine (NAG) have been carried out in aqueous and different aquated organic solvents like CH3OH, CH3CN, dioxane, DMF and their equimolar mixtures by using absorption difference and comparative absorption spectroscopy involving 4f-4f transitions spectra as probe. The results of least squares fit of the energy levels and intensities of the bands are reported in terms of energy interaction and intensity parameters. Various energy interaction parameters like Slater Condon (Fk), Racah (Ek), Lande (x4f), nephelauxetic effect (b), bonding (b1/2) and per cent covalency (d) parameters have been computed to explain the nature of complexation. The changes in the values of oscillator strength (P) and Judd-Ofelt parameters (Tl, l = 2, 4, 6) have been used to investigate the specific correlation between relative intensities and mode of binding for the interaction of Pr(III)-Ala-Gln and Pr(III)-NAG complexes. The comparative absorption difference of different 4f-4f transitions for Pr(III) complexes in different solvents and their equimolar mixtures has also been studied to investigate for the involvement of solvents in complexation.